A thermo‐stable poly(propylene carbonate)‐based composite separator for lithium‐sulfur batteries under elevated temperatures. (8th July 2020) - Huang, Huijia; Zhao, Changjiang; Ding, Fei; Li, Huan; Zhang, Shuoqing; Liu, Xingjiang; Xu, Qiang
Summary: Lithium‐sulfur (Li‐S) batteries have a great potential for the future development of energy industry. However, the high‐temperature performance of Li‐S batteries is still facing great challenge due to the high flammability of the electrolyte, sulfur cathode as well as the separator. The separator modification is an effective method to improve the thermal stability of separator and the electrochemical performance of Li‐S batteries under elevated temperatures. However, the reported methods of separator coating are too complicated to be applied in the industrial production. Here, a novel thermo‐stable composite separator (M‐Celgard‐p), in which a layer of silicon dioxide‐poly (propylene carbonate) based electrolyte (nano‐SiO2 @PPC) with a high ionic‐conductivity of 1.03 × 10 −4 S cm −1 is coated on the commercial Celgard‐p separator, is prepared by using a simple dipping method. Compared to the Li‐S battery assembled with Celgard‐p separator, the M‐Celgard‐p separator combined with a sulfur/polyacrylonitrile (S/PAN) cathode can improve the electrochemical performance of Li‐S batteries, especially their high‐temperature stability. As a result, the (S/PAN)/M‐Celgard‐p/Li cell delivers a high specific capacity of 724.7 mAh g −1 at 1.0 A g −1 after 200 cycles and presents a good rate capability of 1408 mAh g −1 at 1.0 A g −1 and 1216 mAh g −1 at 2.0 A g −1 . More importantly, the (S/PAN)/M‐Celgard‐p/Li cell can exhibit a capacity retention ratio of 69.4% after 200 cycles at 60°C. The M‐Celgard‐p separator with high Li‐ion conductivity can not only block the "shuttle‐effect" of polysulfides during cycling but also enhance the thermal stability under elevated temperatures. This work presents a simple dipping method to prepare composite separator with excellent thermal stability, which enhance the rate performance and cyclic stability of Li‐S batteries under elevated temperatures. We believe this work can provide a new way to develop more reliable Li‐S batteries for practical applications. Abstract : A thermo‐stable separator was prepared by a simple dipping method for Li‐S batteries, in which a layer of silicon dioxide‐poly (propylene carbonate) based electrolyte with a high ionic‐conductivity of 1.03 × 10−4 S cm−1 is coated on the commercial separator. The composite separator can not only block the shuttle of polysulfides but also improve the battery stability under elevated temperatures. As a result, the Li‐S batteries using this separator exhibit high capacity retention of 69.4% after 200 cycles at 60 °C.